Histological effect of commercial sodium cyanide (NaCN) on the thyroid gland of mice (Mus musculus). - Subade, Riza Ortega (1994.)
A study on the effect of cyanide on the thyroid gland of mice was conducted by adding four different amounts of cyanide per kg. of the experimental diet. The levels of cyanide added to the diet were 10, 150, 300, and 600 mg/kg of the experimental diet. A control without cyanide added to the diet was included among the treatments. A total of 15 mice with 3 replicates per treatment were used. The mice were fled for a duration of 31 days, after which they were sacrificed, the thyroid glands were removed and subjected to a histological process. The parameters measured during the examination of the thyroid gland were the follicle diameter size and follicle cell height. The follicle diameter of the thyroid gland of mice, in four different levels of dietary cyanide treatment were then compared to that of the control with mice where their diet do not contain cyanide. The presence of cyanide compound in the diet of mice resulted in an increase in size of the follicles of the thyroid gland which started even at 10 mg/kg of cyanide added to their diet. This increase continued at 150 and 300 mg/kg of cyanide which may be its maximum size for there was no further large sized follicles noted at 600 mg/kg of cyanide (Treatment V). Distortions and delamination of follicles started to manifest at 300 mg/kg of cyanide (Treatment IV), which became predominant in Treatment V (at 600 mg/kg of cyanide). The study showed that cyanide increase follicular size of the thyroid gland. Even at a minimal dose of 10 mg/kg of cyanide, histological changes are already observed. This suggest that the presence of cyanide in the diet could impair the metabolic functions of the gland.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Commercial Sodium Cyanide (NaCN); Thyroid Gland -- Mice